“The Upliftment in status of Women Empowerment in 20th century-A study of Bundelkhand Region Uttar Pradesh and Madhya Pradesh India” - Thakur, Divya Jyoti; Sharma, Dipanker (International Journal of Psychosocial Rehabilitation, 2020)
The status of women suffered from huge changes over last few millennia. There has been great declination in the status of women from ancient to medieval period. The Main cause of degradation of status of women was invasion of India by foreign ruler especially Muslims ruler. Muslim along with them brought their culture with them which in turn resulted the downfall in the position of women in the society. Muslim culture at that time has very low perception towards women. They consider women’s mere an object or property of father, brother and husband. This thought deprives women’s existence as humans. The study of any society is incomplete without the study of role of women in his family, society and nation, equality status of women, Education freedom, and choice of marriage, freedom of practicing their constitutional rights and freedom of fulfilling their duties towards their family, society and nation. India is considered as a nation of Unity in Diversity. In India status of women differ with region. At present we have focus on Bundelkhand region. Bundelkhand region outstretches in two states i.e. Madhya Pradesh and Uttar Pradesh. Our objective of study is to investigate the change in status of women since independence to till date, study of different steps taken by constitution in empowerment of women, changes in views of society towards women, change in their socio-economic status from independence.